Buckham's bombers the Australian airmen who hunted Hitler's deadliest battleship - Baker, Mark (Allen & Unwin, 2024)
"The untold story of one of the finest Australian air crews in World War II, and one of the most dangerous missions of the war in Europe. Bruce Buckham was captain of one of the finest Lancaster crews in Bomber Command in World War II. The Australians were famous for their exploits in the air and infamous for their hijinks on the ground. Buckham's crew flew night after night against heavily-defended targets in Germany risking their lives at the ruthless determination of their commanders, including in the Battle of Berlin, regarded as the bloodiest campaign for Australians in the war. But their most dangerous mission was yet to come. The greatest battleship ever built, and the pride of Hitler's fleet lay in a remote fjord in Norway's far north. Time and again Tirpitz had evaded the hunters, continuing to threaten vital Arctic convoys. By late 1944, her destruction remained a top priority for Churchill. Buckham's crew was hand-picked for the final raids to sink Tirpitz due to their exceptional skill and bravery. In a gripping account, journalist Mark Baker tells the story of one of Australia's most highly decorated World War II pilots and his crew in full for the first time, drawing on extensive interviews with Buckham himself, and other primary sources."--Publisher's description
Keywords: Buckham, Bruce / 1918-2011; Great Britain / Royal Air Force. Bomber Command / Officers / Biography; Tirpitz (Battleship); World War, 1939-1945 / Aerial operations, Australian; World War, 1939-1945 / Aerial operations, British; World War, 1939-1945 / Participation, Australian; World War, 1939-1945 / Personal narratives, Australian; Lancaster (Bomber); Bomber pilots / Australia / Biography; Air pilots, Military / Australia / Biography; Guerre mondiale, 1939-1945 / Opérations aériennes britanniques; Pilotes de bombardiers / Australie / Biographies; Pilotes d'aéronef militaires / Australie / Biographies; Biographies